Determining the prevalence and correlates of COVID-19 booster vaccine hesitancy in the Singapore population following the completion of the primary vaccination series - Tan, Kevin Y. K. (2022)
In response to declining vaccine-induced immunity and the emergence of new COVID-19 variants, COVID-19 booster vaccination programmes have been widely launched in several high-income countries. However, public response has been slow, and scepticism about these programmes is rising in these settings. This study sought to identify the sociodemographic, emotional, and psychological factors associated with COVID-19 booster vaccine hesitancy in Singapore. Derived from a community cohort, 1005 fully vaccinated adults (62.1% female, mean age = 42.6 years) that had not received their COVID-19 booster shots completed an online survey between October and November 2021 on vaccination beliefs, intentions, and behaviours. Results indicated that despite completing the primary COVID-19 vaccination, 30.5% of those surveyed were hesitant about receiving the booster shot (25.9% unsure; 4.7% refused the booster), and 39.2% perceived more vaccine risks than benefits. Multivariable models indicated that a tertiary education, lower COVID-19 threat perception, lower perceived benefits, higher perceived concerns, a decreased need for booster vaccination, and a lower benefit/concerns differential score were associated with higher odds of booster vaccine hesitancy. Success in the primary vaccination series may not warrant widespread public acceptance for recurrent COVID-19 vaccination doses. In addressing booster vaccine hesitancy as restrictive measures and mandates are lifted, health perceptions relevant or unique to booster vaccine uptake should be considered.